2011
DOI: 10.1002/elsc.201000161
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fructose and oxygen gradients on fed‐batch recombinant protein production using Bacillus megaterium

Abstract: Bacillus megaterium expressing a variant of the green fluorescent protein (GFP) was used to investigate the influence of gradients in dissolved oxygen (DO) and fructose concentration on biomass and product formation. For this purpose, several fed‐batch experiments with DO as feed control parameter were performed using suboptimal and optimal adjusted control parameters. In a first approach, suboptimal DO‐feeding was reached by varying randomly the controller output between 10 and 20% of the maximal pumping capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Lower oxygen tension slowed the energy generation of the respiratory chain and the present fructose concentration caused overflow metabolism [44], indicated by the secretion of acetate during growth (Fig. 2 and Additional file 1: Figure S1) which has been described previously [40, 45]. In this study, maximal acetate concentrations of 0.45–0.55 g L −1 were attained in shake flask and bioreactor cultivations, but only 0.25 g L −1 in microtiter plate experiments.…”
Section: Resultsmentioning
confidence: 74%
“…Lower oxygen tension slowed the energy generation of the respiratory chain and the present fructose concentration caused overflow metabolism [44], indicated by the secretion of acetate during growth (Fig. 2 and Additional file 1: Figure S1) which has been described previously [40, 45]. In this study, maximal acetate concentrations of 0.45–0.55 g L −1 were attained in shake flask and bioreactor cultivations, but only 0.25 g L −1 in microtiter plate experiments.…”
Section: Resultsmentioning
confidence: 74%
“…In these studies, it could be shown that overflow metabolites occur due to locally high substrate concentrations. Furthermore, short-term oxygen limitations of the microorganisms could be detected, causing a reduction of biomass and product concentration or the formation of overflow metabolites [14,20,23,25,26,28,30,31,33]. However, also positive effects of short-term oxygen limitation could be noticed as glucose is in excess and, thus, the number of dead cells decreased [14,26].…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, cells are retained in their regions exist simultaneously within the same bioreactor. Studies investigating heterogeneities of nutrients by applying glucose pulse experiments or bioreactors with poor mixed regions were conducted with Saccharomyces cerevisiae [20][21][22][23], Escherichia coli [24][25][26][27] and other bacteria [28][29][30][31][32] and yeast. In these studies, it could be shown that overflow metabolites occur due to locally high substrate concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…A couple of highlights out of the broad spectrum of inspiring talks are presented in this special issue. It includes contributions from numerous hot spots of German and Swiss bioprocess engineering groups in Aachen (Jochen Büchs) 1, Braunschweig (Ezequiel Franco‐Lara) 2, Hamburg (Reiner Luttmann) 3, Kaiserlautern (Ulber) 4, Munich (Dirk Weuster‐Botz and Thomas Becker) 5–7, Senftenberg (Klaus‐Peter Stahmann) 8, Wädenswil/Zurich (Dieter and Regine Eibl) 9 and Dresden with myself 10, 11. Additionally a technical report of one of the leading companies in the field of bioreactor development and production, Satorius Stedim, is included 11.…”
mentioning
confidence: 99%
“…The articles in this issue cover a wide range of scientific topics: Starting with investigations on the influence of gradients and inhomogeneities in the culture medium on the process performance. The publications address gradients in nutrient supply, hydrodynamic cavitations, mixing in single‐used stirred bioreactors, and taking advantage of the volatility of a product for process integrated downstream processing 2, 5, 9, 10. Another paper deals with pressurized cultivations in order to increase the oxygen transfer and plasmid DNA production that is intended to be used as a vaccine 1.…”
mentioning
confidence: 99%